Effects of SID Lys:CP ratios, specialty protein products, and hydrolyzed yeast on nursery pig growth performance, fecal characteristics, and antioxidant status - Smallfield, Jessica (My University, 2025)
This thesis contains three chapters that includes: 1) evaluating the effects of standardized ileal digestible lysine to crude protein (SID Lys:CP) ratios on growth performance of 11- to 25-kg pigs, 2) evaluating the effects of novel specialty soy protein products on growth performance and fecal dry matter (DM) of nursery pigs, and 3) evaluating the effects of hydrolyzed yeast on weanling pig growth performance, fecal characteristics, and stress-related blood antioxidant criteria. Chapter 1 utilized 10,207 nursery pigs in three experiments to determine whether nitrogen (N) is the limiting factor in low protein, amino acid fortified diets, and to evaluate the effects of SID Lys:CP ratios of 11- to 25-kg pigs. Diets formulated to a SID Lys:CP ratio greater than approximately 6.5% decreased feed efficiency (G:F) but adding a N source to low protein diets formulated above this ratio improved G:F. Chapter 2 involved 1,614 pigs in two experiments to evaluate the efficacy of novel specialty soy protein products (soy protein concentrate and thermo-mechanically processed soybean meal) on growth performance and fecal DM of nursery pigs. Ultimately, replacing 25 to 50% of the digestible Lys provided by soybean meal in diets for 5 to 13 kg pigs with specialty soy products improved growth performance, while total replacement resulted in decreased performance. Chapter 3 utilized 360 weanling pigs to evaluate the efficacy of a novel hydrolyzed yeast (HY) product on growth performance, fecal DM, stress-related blood antioxidant criteria, and cytokine production. Overall, feeding 0.04% HY improved G:F. Increasing HY inclusion had no impact on growth performance, but improved early nursery fecal DM. The addition of 0.04% HY with carbadox tended to reduce serum cytokine concentrations. In summary, these experiments provide data on the optimal SID Lys:CP ratio for 11- to 25-kg pigs, the effects of novel soy protein products in nursery pig diets, and the effects of hydrolyzed yeast on nursery pig growth performance, fecal characteristics, stress-related blood antioxidant criteria, and cytokine parameters.
Keywords: Crude protein; Lysine to crude protein ratio; Nursery pig; Hydrolyzed yeast; Specialty soy protein